LEGAL ASPECT PROTECTION ON ONLINE SHOP OF THE THIRD PARTY (Study at CV. Mekar Jaya Persada-The Largest Online Shop in Demak www.Shopee.co.id) - Hartono, Kami; Lestari, Diyda Puji (UNISSULA, 2018)
Technological development nowadays is very fast is a communication technology, which presents a wide selection of forms of technology and sophistication. As a result of the very rapid technological developments such, gradu ally with its own information technology has changed the human life globally in terms of buying and selling online about how the law is not loaded or is described in the statute books of the civil law. So with the development of the sale require the creati on of new legal rules. Online shop in Indonesia today has a lot of users ranging from social media to the online shop of mobile application software - based online shop. The method used is the juridical methods of sociology with emphasis on law is not only s een as regulations or rules, but also includes the operation of law in society , Research shows that buying and selling Legal Aspects Protection on Online Shop with third parties who do online marketplace of Shopee using an escrow service